Degradation characteristics of permafrost under the effect of climate warming and engineering disturbance along the Qinghai–Tibet Highway - Hui Peng; Wei Ma; Yan-hu Mu; Long Jin; Kun Yuan
Based on the monitoring data from 13 typical monitoring sites along the Qinghai–Tibet Highway, the degradation characteristics of the permafrost under asphalt pavement and natural ground surface were analyzed with considerations of climate warming and engineering disturbance. Results indicated that the mean annual thawing indexes (MATI) and mean annual freezing indexes (MAFI) of asphalt pavement ranged from 895 to 2,540 °C days and from 290 to 1,097 °C days, respectively, while the MATI and MAFI of natural ground ranged from 144 to 1,550 °C days and from 127 to 1,544 °C days, respectively. In warm seasons, average temperatures of asphalt pavement were 0.76–8.58 °C higher than that of natural ground, while in cold seasons, average temperatures of asphalt pavement were 0.22–4.19 °C lower than that of natural ground. Both natural permafrost table and artificial permafrost table were continuously declining through 1995–2011. Under the effect of climate warming, the active layer thickness (ALT) increased about 0.44 m, with an average increasing rate of 3.42 cm a −1 in cold permafrost regions [the mean annual ground temperature lower than −1.0 °C (MAGT > −1.0 °C)], while in warm permafrost regions (MAGT > −1.0 °C), the ALT increased about 0.68 m, with an average increasing rate of 5.72 cm a −1 . Under the effect of engineering disturbance, the ALT increased 1.38 m in cold permafrost regions, with an average increasing rate of 12.28 cm a −1 , while in warm permafrost regions, the ALT increased 1.32 m, with an average increasing rate of 11.18 cm a −1 . Meanwhile, changes in permafrost temperature under asphalt pavement were different from that under natural ground. The warming rate in permafrost under asphalt pavement at 6, 10 and 15 m depths was 0.024, 0.022 and 0.02 °C a −1 , respectively, while the three values under natural ground were 0.016, 0.013 and 0.013 °C a −1 . From these results above, it can be concluded that influences from climate warming on permafrost degradation in warm permafrost region were greater than that in cold permafrost region, and influences from engineering disturbance on permafrost degradation in warm permafrost region were less than that in cold permafrost region. Copyright Springer Science+Business Media Dordrecht 2015 Qinghai–Tibet Highway (QTH), Permafrost degradation, Active layer thickness, Permafrost temperature